2022
DOI: 10.1017/langcog.2022.14
|View full text |Cite|
|
Sign up to set email alerts
|

Foreign to whom? Constraining the moral foreign language effect on bilinguals’ language experience

Abstract: The moral foreign language effect (MFLE) describes how people’s decisions may change when a moral dilemma is presented in either their native (NL) or foreign language (FL). Growing attention is being directed to unpacking what aspects of bilingualism may influence the MFLE, though with mixed or inconclusive results. The current study aims to bridge this gap by adopting a conceptualization of bilingualism that frames this construct as a composite and continuous measure. In a between-group analysis, we asked 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
4
10
0
Order By: Relevance
“…This work adds to a growing literature investigating graded effects of separable dimensions of language experience on previously reported psycholinguistic phenomena (Privitera et al, 2022a(Privitera et al, , 2022b. We did not observe an MFLE consistently across all dilemmas, replicating the null and mixed findings of some previous studies (Čavar & Tytus, 2018;Costa et al, 2014;Del Maschio et al, 2022b;Wong & Ng, 2018). In fact, an MFLE was only observed on the Organ Transplant dilemma.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This work adds to a growing literature investigating graded effects of separable dimensions of language experience on previously reported psycholinguistic phenomena (Privitera et al, 2022a(Privitera et al, , 2022b. We did not observe an MFLE consistently across all dilemmas, replicating the null and mixed findings of some previous studies (Čavar & Tytus, 2018;Costa et al, 2014;Del Maschio et al, 2022b;Wong & Ng, 2018). In fact, an MFLE was only observed on the Organ Transplant dilemma.…”
Section: Discussionsupporting
confidence: 85%
“…The Organ Transplant and related Surgeon and Transplant dilemmas are not widely used across previous studies (Del Maschio et al 2022a). To the best of our knowledge, only one study has reported a significant MFLE on this dilemma (Shin & Kim, 2017) with most reporting null results (Čavar & Tytus, 2018;Del Maschio et al, 2022b;Wong & Ng, 2018) although null results are contentious (Białek & Fugelsang, 2019). In the Organ Transplant dilemma, the participant is taking the perspective of a doctor who must make a choice that violates the norms associated with that role (i.e., causing harm to a patient).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations